Змістова особливість та емпірична інтерпретація патріотичності українців (на прикладі жителів міста Луцька) - Сальнікова, Світлана Анатоліївна; Сальникова, Светлана Анатольевна; Salnikova, Svitlana А.; Гончар, Ірина Анатоліївна; Гончар, Ирина Анатольевна; Honchar, Iryna A. (Східноєвропейський національний університет імені Лесі Українки, 2013)
У статті проаналізовано особливості формування та прояву патріотичності українців крізь призму соціокультурної спадкоємності. За допомогою концептуалізації поняття «патріотичність» розроблено систему емпіричних індикаторів. Апробацію підходу до вимірювання патріотичності населення здійснено на вибірці жителів міста Луцька (N=420, яку репрезентовано за статтю, віком та освітою). Відповідно, основний акцент зроблено на емпіричній інтерпретації їхньої патріотичності (одновимірний аналіз). Peculiarities of formation and manifestation of Ukrainian patriotism through the prism of social and cultural succession are analyzed. Empirical interpretation of the patriotism made on a sample population of Lutsk (N = 420, the sample is representative by gender, age and education). According to onedimensional analysis obtained the following results: (1) the level of subjective patriotism of city residents is 43 %. Ukrainian patriotism is no explicit states character, it connect with the traditions which observed by conviction rather than as needed (60,2–85,4 %). Preservation of national originality (84,7 %) is directly related with the preservation of native wildlife (86,6 %) (c=0,7, Sig.=0,01). The main integrating factors are common language (44 %), customs and traditions (43%), but the common religion is weaker a unifying factor (28 %); (2) the degree of integration in social life (less than 25 %) indicates a civic passivity of Ukrainian, the cumulative rate of personal responsibility for the fate of the country (40 %) – the stability of paternalistic expectations.
Content’s Peculiarity and Empirical Interpretation of the Ukrainian Patriotism (Case of City Lutsk Population)
Keywords: патріотичність; українська патріотичність; концептуалізація патріотичності; державна патріотичність; громадянська пасивність; patriotism; Ukrainian patriotism; conceptualization of patriotism; state patriotism; civic passivity